50/50 oil/water emulsion stabilized by pea protein isolate microgel particles/xanthan gum complexes and co-emulsifiers. (January 2023) - Li, Sisheng; Jiao, Bo; Faisal, Shah; Zhang, Yu; Wu, Bicong; Li, Wei; Shi, Aimin; Liu, Hongzhi; Wang, Qiang
Abstract: Properties of 50/50 oil/water emulsion stabilized by pea protein isolate microgel particles (PPIMP)/xanthan gum (XG) and co-emulsifiers were evaluated. Three surfactants with different charging characteristics (lauric arginate, LAE, cationic surfactant; diacetyl tartaric acid esters of mono- and diglycerides, DATEM, nonionic surfactant; sodium stearyl lactate, SSL, anionic surfactant) were selected to co-stable emulsion systems with PPIMP/XG, respectively. The emulsions stabilized by PPIMP/XG with LAE reached the minimal droplet size (21.5 μm). The increased addition of either DATEM or SSL decrease the droplet size of emulsion (except for the 0.8 wt% SSL). The emulsions showed lower apparent viscosity at higher DATEM concentration, whereas the vice-versa was observed in the prepared emulsions with SSL. Surfactants with different charge properties can affect the antioxidant properties of the emulsions. All the emulsions containing LAE, DATEM, or SSL can inhibit oxidation by adjusting the concentration, which could be confirmed in a study on the retention of resveratrol. This study provides a deeper insight into the emulsions co-stabilized by different emulsifiers and can be applied in edible O/W emulsions in the food industry like egg-free mayonnaise. Graphical abstract: Image 1 Highlights: Pea protein microgels and xanthan gum can obtain stable 50 wt% O/W emulsion. 0.02 wt% lauric arginate in emulsion reduced droplet size and increased viscosity. Non-ionic surfactant fell emulsion's viscosity and G′, anionic one did opposite. The existence of surfactants could enhance the oxidation stability of emulsions.